Artists' handbook. - Ceuleers, Jan; Focillon, Henri; Exhibition. Hands of art. SMAK (Stedelijk Museum voor Actuele Kunst) Gent. 2008-01-26. 2008-03-16 (Antwerpen Gent : Galerie Ronny Van de Velde Antwerpen Ludion Gent SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2007)
Van den Abeele, Michael ; Abramovic, Marina ; Adams, Ansel ; Agam, Yaacov ; Albers, Josef ; Alcalay, Albert ; Alechinsky, Pierre ; Antes, Horst ; Arad, Ron ; Archipenko, Aleksandr ; Armitage, Kenneth ; Arocha, Carla ; Aronson, Boris ; Arp, Hans (Jean) ; Artschwager, Richard ; Atelier van Lieshout ; Baechler, Donald ; Baldessari, John ; Barrio, Artur ; Baskin, Leonard ; Bayer, Herbert ; Bearden, Romare ; Becher, Bernd & Hilla ; Bellinkx, Ruben ; Ben ; Bergman, Anna-Eva ; Berthold, Joachim ; Bertoia, Harry ; Bervoets, Fred ; Beuys, Joseph ; Bidlo, Mike ; Bijl, Guillaume ; Bill, Max ; Birnbaum, Dara ; Birolli, Renato ; Bischof, Werner ; Blomstedt, Aulis ; Boël, Delphine ; Bogart, Bram ; Borremans, Michaël ; Bouché, Louis ; Bourgeois, Louise ; Braeckman, Dirk ; Brassaï ; Breton, Elisa ; Brindisi, Remo ; van den Broek, Koen ; Broodthaers, Marcel ; De Bruyckere, Berlinde ; Buggenhout, Peter ; Bunuel, Luis ; Bury, Pol ; De Buysere, Saar ; Van Caeckenbergh, Patrick ; Cahun, Claude ; Calder, Alexander ; Capogrossi, Giuseppe ; Carlier, Jan ; Caro, Anthony ; Carreno, Mario ; Cattelan, Maurizio ; César ; Chagall, Marc ; Charlier, Jacques ; Cheney, Sheldon ; De Chirico, Giorgio ; Christie, Cedric ; Cladders, Johannes ; Claerbout, David ; Claus, Hugo ; Clergue, Lucien ; De Cock, Jan ; Coggeshall, Calvert ; Combas, Robert ; Copley, William ; Corberó, Xavier ; Covarrubias, Miguel ; Cuevas, Jose Luis ; De Cupere, Peter ; Daems, Anne ; Dans, Michael ; Davis, Stuart ; Deleu, Luc ; Delrue, Ronny ; Delvoye, Wim ; Denmark ; de Diego, Julio ; Dillemans, Sam ; Dimitrijevic, Braco ; Dohmen, Léo ; Domela, César ; Dondeyne, Luc ; Dorazio, Piero ; Downsbrough, Peter ; Dreier, Katherine S. ; Dubuffet, Jean ; Duchamp, Marcel ; Dujourie, Lili ; Dumas, Marlene ; Dumitrescu, Natalia ; etc.
korte biog.
publ. SMAK : zie kast leeszaal
Engels
boek